Reviews (Zygon, 2006)
Mind in a Physical World: An Essay on the Mind-Body Problem and Mental Causation. By Jaegwon Kim. Sacred Cosmos: Christian Faith and the Challenge of Naturalism. By Terence L. Nichols. The Faith of Biology & The Biology of Faith: Order, Meaning, and Free Will in Modern Medical Science. By Robert Pollack.